(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the problem of the purposeful formation of a high quality of ensuring economic growth, in order to reveal its full description, taking into account the circumstances that, in our opinion, require general methods for the development of the economy, firstly, a systematic approach to its definition, and secondly, a special abstraction with a clear depth in the research of economic growth approach is required. At the same time, the article provides an analysis of economic growth indicators, a detailed study of problems in the field, and scientifically based proposals.